2008
DOI: 10.1128/jvi.02647-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transcription and DNA Replication by the Papillomavirus E8⁁E2C Protein Is Mediated by Interaction with Corepressor Molecules

Abstract: Papillomavirus genomes replicate as nuclear plasmids at a low copy number in undifferentiated keratinocytes. Papillomaviruses encode the E1 and E2 proteins that bind to the origin of replication and are required for the activation of replication. In addition to E2, several papillomaviruses express an E8ˆE2C protein, which is generated by alternative splicing and functions as a transcriptional repressor and inhibitor of the E1/E2-dependent replication of the viral origin. Previous analyses suggested that the E8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 46 publications
5
46
0
Order By: Relevance
“…While 31E8^E2C was also found to interact with TRIM28 and SETDB1 (1), siRNA knockdown experiments indicated that these proteins do not contribute to the repression of the HPV URR by 31E8^E2C (31). Furthermore, while HDAC inhibitors relieved repression by 31E8^E2C, this was not the case for the KOX1 KRAB domain (1,24). These data suggest that the repression of the URR by E8^E2C and KRAB-E2C is achieved by the recruitment of different transcription factors and possibly by different repression pathways.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…While 31E8^E2C was also found to interact with TRIM28 and SETDB1 (1), siRNA knockdown experiments indicated that these proteins do not contribute to the repression of the HPV URR by 31E8^E2C (31). Furthermore, while HDAC inhibitors relieved repression by 31E8^E2C, this was not the case for the KOX1 KRAB domain (1,24). These data suggest that the repression of the URR by E8^E2C and KRAB-E2C is achieved by the recruitment of different transcription factors and possibly by different repression pathways.…”
Section: Discussionmentioning
confidence: 62%
“…The transcriptional-repression activity of E2 has been linked to the interaction with the cellular Brd4, SMCX, and EP400 proteins (35,45). In contrast, the transcriptionalrepression activity of 31E8^E2C has been linked to the interaction of the E8 domain with cellular corepressors, such as HDAC3 and the N-CoR protein (1,31). The KRAB domain of KOX1 represses transcription through the recruitment of the corepressor TRIM28/KAP1/TIF1␤/KRIP1, heterochromatin protein 1 (HP1) alpha, HP1 gamma, and the histone methyltransferase SETDB1 (12,23,25,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HPV31 E8/E2 protein represses transcription and extra-chromosomal replication; many interactions responsible for these repressive functions are described. [41][42][43] However, the HPV31 E8 and BPV1 E8 proteins belong to different E8 clades (Puustusmaa and Abroi, manuscript in preparation). In addition, the subcellular localization of HPV31 E8/E2 has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter E2s antagonize the function of full-length E2 by competing for E2 DNA binding sites. In addition, the E8 of HPV 31 E8/E2 protein itself is a transcriptional repressor domain that functions independently of binding site competition inhibiting transcription and DNA replication by interacting with corepressor molecules such as NCoR1/HDAC3, the histone methyltransferase SETDB1, and the TRIM28 protein (Ammermann et al, 2008;Powell et al, 2010). The full-length and truncated E2 proteins are able to form dimers through their common Cterminal DNA-binding-dimerization domain (McBride et al, 1989).…”
Section: E2 Repressors and Heterodimersmentioning
confidence: 99%